The Effect of Dry Needling of Trigger Points in Forearm's Extensor Muscles on the Grip Force, Pain and Function of Athletes with Chronic Tennis Elbow - Zahra Etminan; Mohsen Razeghi; Farahnaz Ghafari Nezhad (Shiraz University of Medical Sciences, 2019)
Background: Tennis elbow syndrome (TES) is mainly known by having pain in the external side of the elbow. Physiotherapy plays an effective role in the treatment of this syndrome. Dry needling is a less invasive, novel, and inexpensive method that shows its therapeutic effects in a shorter time in comparison with the other physiotherapy methods. Effect on tough bands, circulation, and environmental and central neurophysiological effects are some mechanisms by which dry needling poses its effects. The aim of this study was to study the effect of adding dry needling to routine physiotherapy methods in order to improve grip strength and function and reduce pain, as well as to decrease costs and treatment duration for treating tennis elbow syndrome. Methods: Forty four athletes aged 18 to 40 years old who had exercise or match for at least 3 sessions per week (for a sum of 6 hours per week), and were detected to have tennis elbow syndrome lasting more than 3 months were recognized and classified into two groups. The first group received physiotherapy including ultrasound, deep friction massage, and muscle stretching and strengthening exercises. The second group received dry needling in addition to physiotherapy treatment. Therapeutic duration was 3 weeks in each group and 3 sessions in each week. The patient rate elbow evaluation questionnaire (PREE) was completed at the beginning of treatment and the beginning of the second and third weeks, as well as at the end of the third week; grip strength was measured at the mentioned times as well. One week after the end of the therapeutic period, patients were reevaluated for the reliability rate of the treatment outcomes. For analysis of data obtained for the study, repeated measure test, Mixed ANOVA, and Paired T-test statistical tests were used. Results: Results showed that all evaluated variables (including pain, function, and grip strength) were improved in the patients of both groups after completion of the therapeutic period (P<0.0001). Comparison of the two groups showed a significant difference in the pain variable at the seventh session with P<0.0001, the ninth session with P=0.006, and one week after the end of treatment with P<0.001, and the performance variable at seventh sessions with P<0.0001, ninth sessions with P=0.006, and one week after the end of treatment with P<0.0001, respectively. The pain reduction and function increase rates were higher in the group that received dry needling in addition to physiotherapy in comparison with the group that received physiotherapy after the seventh session. Regarding grip strength variable, the mean of groups was different, though the effect of these two methods in the enhancement of grip strength was not statistically significant (P=0.09). Moreover, regarding the results obtained for the group that received physiotherapy in addition to dry needling, the pain variable reduced in a shorter time in comparison with the other group. Conclusion: With regard to the results mentioned above, both therapeutic methods resulted in an improvement in the studied variables in a comparison that was performed before and after treatment. Moreover, in comparison with the single physiotherapy, using dry needling in addition to physiotherapy had a more powerful effect in improving the studied variables. Therefore, it could be said that using dry needling in addition to other therapeutic methods results in the facilitation of treatment process in the patients, and can reduce their therapeutic costs.